Kunst Unternehmen Kunst: Die Funktion der Kunst in der postfordistischen Arbeitswelt - Mir, Emmanuel (transcript, 2014)
Increasing productivity through art? Emmanuel Mir questions the varieties of neo-liberal utilization of art.